Modification of Plasmids and Cry Genes of Bacillus thuringiensis subsp. kurstaki HD-I After Treatment With Ethylmethanosulfonate (EMS) and UV Light - Jusuf, Eddy (BRIN, 2004)
Bacillus thuringiensis subsp. kurstaki HD-1 is a potential insecticidal bacterium producing five type of a-endotoxin crystal proteins. This bacterium is widely commercialized due to its wide spectrum toxicity against both Lepidopteran and Dipteran larvae. The objective of this work was to create autolysin deficient mutant causing cell fails to lyse. This mutant yield intact cells within spore and a-endotoxin crystal protein protected inside, from which an undamaged active bio-insecticide would be obtained. Two methods of mutagenesis, 2% of ethylmethanosulfonate and 10, 25, and 50 second of UV light exposure, resulted in mot (loss of motility) mutation. Observation showed that 14 of 20 survived mutants have lost some of its plasmids (varied from one to five). while the other six maintained their plasmids. By employing the polymerase chain reaction (PCR) the change on the cry genes was studied.